ALCOHOL AND ARTERIAL HYPERTENSION - O. D. Ostroumova; E. V. Saperova (Рациональная фармакотерапия в кардиологии)
The article considers the questions of the relationship between the amount of the consumed alcohol, the type of alcoholic beverage, pattern of alcohol consumption and the blood pressure level. The article presents data on the positive effect of alcohol intake restrictions and recommendations for permissible limits of alcohol consumption. New possibilities of drug therapy aimed at limiting alcohol consumption are being reported.